(untitled) (Revista Archai, 2024)
In this paper, we aim to explore Aristotle’s analysis of friendship by examining its three objects of friendship - virtue, utility, and pleasure. We will also explain why these three objects of friendship pose a challenge to defining friendship as a common and singular entity, namely, as a reciprocal and conscious benevolence that has practical effects. It is shown that the objects of friendship are part and parcel of the kind of personal relationship friendship is, making it impossible to provide a common definition.